2012
DOI: 10.2110/palo.2011.p11-036r
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Water Incised Valley Deposits at the Ediacaran-Cambrian Boundary in Southern Namibia Contain Abundant Treptichnus Pedum

Abstract: Valley-filling deposits of the Nama Group, southern Namibia, record two episodes of erosional downcutting and backfill, developed close together in time near the Ediacaran-Cambrian boundary. Geochronological constraints indicate that the older valley fill began 539.4 ± 1 Ma or later; the younger of these deposits contains unusually well-preserved populations of the basal Cambrian trace fossil Treptichnus pedum. Facies analysis shows that T. pedum is closely linked to a nearshore sandstone deposit, indicating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 10 1995). In the Witputs Sub-Basin the Ediacaran-Cambrian (E-C) boundary is marked by a regionally extensive erosional unconformity (Germs, 1983;Saylor and Grotzinger, 1996;Narbonne et al, 1997;Grotzinger et al, 1995) overlain by an incised-valley fill sequence that contains the earliest Cambrian trace fossil Treptichnus pedum (Wilson et al, 2012).…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…A c c e p t e d M a n u s c r i p t 10 1995). In the Witputs Sub-Basin the Ediacaran-Cambrian (E-C) boundary is marked by a regionally extensive erosional unconformity (Germs, 1983;Saylor and Grotzinger, 1996;Narbonne et al, 1997;Grotzinger et al, 1995) overlain by an incised-valley fill sequence that contains the earliest Cambrian trace fossil Treptichnus pedum (Wilson et al, 2012).…”
Section: Geological Settingmentioning
confidence: 99%
“…However, ash beds in the overlying units (Figure 2) provide robust U-Pb zircon age constraints ranging from 548.8 ± 1 Ma in the Hoogland Member of the Kuibis Subgroup revised to 547.32 ± 0.31 Ma by Schmitz et al 2012) to 538.18 ± 1.24 Ma in the upper part of the Schwarzrand Subgroup (Grotzinger et al, M a n u s c r i p t 10 1995). In the Witputs Sub-Basin the Ediacaran-Cambrian (E-C) boundary is marked by a regionally extensive erosional unconformity (Germs, 1983;Saylor and Grotzinger, 1996;Narbonne et al, 1997;Grotzinger et al, 1995) overlain by an incised-valley fill sequence that contains the earliest Cambrian trace fossil Treptichnus pedum (Wilson et al, 2012). Therefore, the Nama Group section spans ~10 Myr and extends to beyond the ProterozoicCambrian transition (Saylor et al, 1998;Ries et al, 2010).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…An ash bed in the lower carbonate package of the Urusis Formation has been dated by U-Pb geochronology at 545.1 + 1 Ma, and an ash bed approximately 85 m below the investigated fossil beds at 543.3 + 1 Ma ([22]-see figure 1; recalculated to 540.61 + 0.67 Ma in [23]). An erosive unconformity overlain by complex valley-filling deposits of the earliest Cambrian Nomtsas Formation cuts down through the Ediacaran strata, although the physical unconformity itself is not well exposed on Swartpunt Farm [18,22,24]. Nomtsas strata in the Swartkloofberg Farm directly north of Swartpunt contain an ash bed dated to 539.4 + 1 Ma ( [22]; recalculated to 538.18 + 1.11 Ma in [23]).…”
Section: Introductionmentioning
confidence: 99%
“…These projections signify the behavioural movement of the animal. Wilson et al (2012) suggested the functional biology of priapulids in two ways: a) the animal might have lived infaunally to avoid predation or desiccation, and appeared on the surface episodically to feed and receive oxygen; and b) the animal might have been a deposit feeder that surfaced regularly to exchange gases and perhaps to disperse eggs, sperm or fertilized eggs. The latter appears more plausible because if the priapulid were able to find food on the surface then there is no valid reason for them to build three-dimensional burrows, although the safety from other predators could be the reason in that case the burrow system reflects the escape mechanism from predation.…”
Section: Palaeobiologymentioning
confidence: 99%